2005
DOI: 10.3748/wjg.v11.i6.903
|View full text |Cite
|
Sign up to set email alerts
|

Tumor metastasis and the reciprocal regulation of heparanase gene expression by nuclear factor kappa B in human gastric carcinoma tissue

Abstract: NF-kappaB RelA (p65) activation was related with increased heparanase gene expression and correlated with poor clinicopathological characteristics in gastric cancers. This suggests NF-kappaB as a major controller of the metastatic phenotype through its reciprocal regulation of some metastasis-related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Here, we found the NF-kB subunit RelA to be overexpressed in roughly half of a large set of pancreatic adenocarcinomas analysed. Overexpression of cytoplasmic and/or nuclear RelA in tumour tissue has been previously observed in larger study cohorts of gastric (Sasaki et al, 2001;Yamanaka et al, 2004;Cao et al, 2005;Lee et al, 2005), prostate (Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004; Figure 2 Kaplan -Meier survival curves in dependence of clinicopathological factors and RelA/p65 expression patterns. Overall survival dependent on nodal status (A) and grade (B).…”
Section: Discussionmentioning
confidence: 59%
“…Here, we found the NF-kB subunit RelA to be overexpressed in roughly half of a large set of pancreatic adenocarcinomas analysed. Overexpression of cytoplasmic and/or nuclear RelA in tumour tissue has been previously observed in larger study cohorts of gastric (Sasaki et al, 2001;Yamanaka et al, 2004;Cao et al, 2005;Lee et al, 2005), prostate (Fradet et al, 2004;Ismail et al, 2004;Ross et al, 2004; Figure 2 Kaplan -Meier survival curves in dependence of clinicopathological factors and RelA/p65 expression patterns. Overall survival dependent on nodal status (A) and grade (B).…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, it has been reported that NF-κB activation upregulates HPSE expression in several tumors [9][10][11][12] . Therefore, we further investigated the relationship between HPSE and NF-κB in melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the relationship between HPSE and NF-κB is under controversial. Previous data reported that NF-κB activation upregulates HPSE expression in several tumours [9][10][11][12] . Recently, focusing on the regulatory relationship between HPSE and NF-κB in glioblastoma cells, questioned their connection 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor κB (NFκB) is a eukaryotic transcription factor involved in a wide range of cellular processes in response to stimuli. A study on gastric carcinoma reported a positive correlation between NFκB and heparanase expression (20). We investigated whether NFκB expression is correlated with heparanase expression in glioblastoma and, if so, how NFκB expression would be regulated.…”
Section: Introductionmentioning
confidence: 99%